Victim Sensitivity and Its Neural Correlates Among Patients With Major Depressive Disorder - Wang, Xiaoming; Cui, Shaojuan; Wu, Michael Shengtao; Wang, Yun; Gao, Qinglin; Zhou, Yuan (Frontiers in Psychiatry, 2020)
Background: Dysfunctional beliefs about self prevail in the development of depressive symptoms, but it remains unclear how depressed patients respond to unfair treatment, both dispositionally and neutrally. The present research is an attempt to explore the difference in sensitivity to injustice as a victim, and its neural correlates in patients with major depressive disorder (MDD) versus healthy controls. Methods: First episodic, drug naïve patients with MDD (n = 30) and a control group (n = 30) were recruited to compare their differences in victim sensitivity. A second group of patients with MDD (n = 23) and their controls (n = 28) were recruited to replicate the findings and completed resting-state functional magnetic resonance imaging (fMRI) scanning. Spontaneous brain activity measured by fractional amplitude of low-frequency fluctuation (fALFF) was used to characterize the neural correlates of victim sensitivity both in patients and healthy controls. Results: Higher victim sensitivity was consistently found in patients with MDD than healthy controls in both datasets. Victim sensitivity was positively correlated with the fALFF in the right dorsolateral prefrontal cortex (DLPFC) in the patients with MDD, but this relationship was reversed in healthy controls. Conclusions: The patients with MDD show higher sensitivity to injustice as a victim, which may be independent of their disease course. The MDD patients differ from healthy controls in the neural correlates of victim sensitivity. These findings shed lights on the linkage between cognitive control subserved by the DLPFC and negative bias towards self implicated by higher victim sensitivity among the depressed patients.